1987
DOI: 10.1002/pssa.2211030204
|View full text |Cite
|
Sign up to set email alerts
|

Electron Diffraction of Translation Interface Modulated Structures

Abstract: Expressions are derived for the kinematical amplitudes of a perfect crystal, modulated by planar translation interfaces. The model is generalised so as to account for longitudinal and transversal relaxation effects at the interfaces and for non‐equidistant interface distributions. The cases of short range order (nearest neighbour correlation) and long range order (uniform sequences) are treated in detail. The results can be applied to antiphase boundaries in long period superstructure alloys as well as to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…It is well known that a broad class of structures can be interpreted as modulated by the periodic occurrence of translation interfaces. It has been illustrated that it is possible to characterize geometrically this kind of structure from ED patterns by applying the fractional shift method (16,17). It can be shown that in the kinematical approximation for electron diffraction a periodic modulation in a direction n with a period d of translation interfaces and characterized by a displacement vector R gives rise to satellite reflections at reciprocal lattice positions g given by…”
Section: Interpretation Of the Electron Diffraction Results As An Intmentioning
confidence: 99%
“…It is well known that a broad class of structures can be interpreted as modulated by the periodic occurrence of translation interfaces. It has been illustrated that it is possible to characterize geometrically this kind of structure from ED patterns by applying the fractional shift method (16,17). It can be shown that in the kinematical approximation for electron diffraction a periodic modulation in a direction n with a period d of translation interfaces and characterized by a displacement vector R gives rise to satellite reflections at reciprocal lattice positions g given by…”
Section: Interpretation Of the Electron Diffraction Results As An Intmentioning
confidence: 99%
“…The satellite spots closest to these spots (indicated by crosses in Fig. 5 d) will be the most intense ones (Van Landuyt et al 1970;D. van Dyck et al 1987).…”
Section: Diffraction Patternsmentioning
confidence: 99%
“…The displacement vector for the CS planes was deduced from the ED patterns as R = 1/2 [110] p + 1/ 3 [001] p by measuring the fractional shifts h R for the satellite reflections (Figure 1 b). [10,11][+] Closer inspection of the [010]* The new structure is derived from the perovskite structure by a periodic insertion of (104) (Figure 3 b). Pb atoms are positioned inside the resulting channels, where space is available for their lone 6s 2 electron pairs.…”
mentioning
confidence: 99%